Spanish Modernity and Roman Antiquity: Between Theatrical Revival and Political Transformation (1920-1944) - Balaskas, Vasileios (Coimbra University Press, 2023)
The classical tradition was gradually introduced to the Spanish public as a way to reach European modernity since the late 19th century. By popularizing Roman texts and monuments, Spanish intellectuals and national institutions established a national archive of heritage that could serve socio-cultural demands. At the same time, state intervention in the revival of classical drama shaped the reception of antiquity and conditioned its socio-political scope. In this article, I analyze how Spanish institutions and political representatives exploited classical heritage and produced the first ancient drama productions at Roman venues in the 1930s as socio-political statements. By engaging with archival material and historical sources, I explore the different reuses of these monuments and the afterlife of productions organized there. Finally, during Franco’s regime and the rise of the Falange until the mid-1940s, their appropriation to display power consolidated its significance as an ideological and political apparatus of the Spanish state.
Keywords: Teatro clásico; Teatro español - Influencia clásica; Estética de la recepción; Política en el arte - España - S. XX; Classical tradition; Falange; Classical reception; Graeco-roman drama; Spanish theatre